Determinants of capital structure performance of property developer companies in Malaysia / Nur Iylia Inani Muhammad Sharif - Muhammad Sharif, Nur Iylia Inani (2016)
This research is about determinants that affecting capital structure performance of property developers companies in Malaysia. The sample of this study are five top public companies that listed in Bursa Malaysia. The period of this study is approximately 8 years range from 2005 until 2014. The collected data was tested using E-views 7.0. Capital structure divided into two major components, debt and equity financing whilst only leverage financing was picked to become subject in this investigations. To determine the optimal leverage to invest in leverage, debt ratio was used as dependent variable. Besides that, five factors that influence capital structure performance were detached including tax rate, liquidity and profitability, market interest rate, and growth rate. Based on regression analysis, the result shows that there is a significant relationship between all three variables with capital structure performance.